PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA FISIK DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN COK KONFEKSI DENPASAR - Vijaya, I Dewa Gede Ngurah Eka Tvam; Sriathi, A.A. Ayu (E-Jurnal Manajemen, 2015)
This research was conducted on employees Cok Confections Denpasar. Sample size of 40 employees Cok Confections Denpasar with saturated sampling method, where the method is to use the entire population of the research samples. Data was collected through questionnaires that using 5-point Likert scale to measure the 18 indicators. The analysis technique used is multiple linear regression analysis, simultaneous test, test and test partial dominant influence. The results showed that transformational leadership positive and significant effect on the performance of employees at Denpasar Confections Cok significance level 0,019 . Second, the physical work environment positive and significant effect on the performance of employees at Denpasar Confections Cok significance level 0,000 . Third, compensation positive and significant impact on the performance of employees at Denpasar Confections Cok significance level 0,018 .
Keywords: kepemimpinan transformasional; lingkungan kerja fisik; kompensasi; kinerja karyawan